Protein hydrolysates enhance recovery from drought stress in tomato plants: phenomic and metabolomic insights - Leporino, Marzia; Rouphael, Youssef; Bonini, Paolo; Colla, Giuseppe; Cardarelli, Mariateresa (Frontiers in Plant Science, 2024)
High-throughput phenotyping technologies together with metabolomics analysis can speed up the development of highly efficient and effective biostimulants for enhancing crop tolerance to drought stress. The aim of this study was to examine the morphophysiological and metabolic changes in tomato plants foliarly treated with two protein hydrolysates obtained by enzymatic hydrolysis of proteins from Malvaceae (PH1) or Leguminosae (PH2) in comparison with a control treatment, as well as to investigate the mechanisms involved in the enhancement of plant resistance to repeated drought stress cycles. A phenotyping device was used for daily monitoring morphophysiological traits while untargeted metabolomics analysis was carried out in leaves of the best performing PH treatment based on phenotypic results. PH1 treatment was the most effective in enhancing plant resistance to water stress due to the better recovery of digital biomass and 3D leaf area after each water stress event while PH2 was effective in mitigating water stress only during the recovery period after the first drought stress event.Metabolomics data indicated that PH1 modified primary metabolism by increasing the concentration of dipeptides and fatty acids in comparison with untreated control, as well as secondary metabolism by regulating phenols. In contrast, hormones and compounds involved in detoxification or signal molecules against reactive oxygen species were down-regulated in comparison with untreated control. The above findings demonstrated the advantages of a combined phenomics-metabolomics approach for elucidating the relationship between metabolic and morphophysiological changes associated with a biostimulant-mediated increase of crop resistance to repeated water stress events.